The more things change, the more things stay the same: maternal attitudes 3 to 18 months postpartum. (6th May 2016) - Cost, Katherine T.; Plamondon, André; Unternaehrer, Eva; Meaney, Michael; Steiner, Meir; Fleming, Alison S.; ,
Abstract: Aim: Becoming a parent precipitates changes in new mothers' psychological and social domains. Previous literature has focused exclusively on pregnancy and the early postpartum, but parenting is an evolving process, necessitating adaption to changing circumstances. We extended previous literature and investigate the changes in the postpartum from 3 to 18 months that occur in maternal attitudes. Methods: Using the Childbearing Attitudes Questionnaire, we collected data on mothers' ratings of maternal worries, self‐efficacy, mother–infant bonding, relationship with the partner and interest in sex ( n = 171 women). Data were analysed with a latent growth curve. Results: Results demonstrated stability in all maternal attitudes after 3 months postpartum. Further, different maternal attitudes are affected by different variables. Maternal worries and self‐efficacy are associated with parity, postpartum depression and child temperament. Interestingly, a negative evaluation of the relationship with the partner was only associated with breastfeeding status, while interest in sex was associated with parity, socio‐economic status (SES) and depressive symptoms. Conclusion: Despite general stability, different maternal attitudes related to different sets of variables. These patterns of attitudes in relation to relevant variables are discussed in terms of the literature on self‐efficacy and gender roles, with important implications for clinical interventions.